Investigation of the biological role of iASPP in vivo - Notari, M (2011)
The p53 family of transcription factors, which comprises the products of the TP53, TP63 and TP73 genes, is at the hub of different signalling pathways that determine the fate of a cell. In vitro, the p53 family posses a tumour suppressive function. However, in vivo, although p53-deficient mice develop spontaneous tumours, p73 and p63 KO animals show defects in neuronal and epidermal development, respectively. The ASPP family of proteins also consists of three members: ASPP1, ASPP2 and iASPP. They are evolutionarily conserved binding partners and specific regulators of p53-, p63- and p73- mediated apoptosis in vitro. In contrast to ASPP1 and ASPP2, the biological significance of iASPP in vivo and the possible interaction with p53 family members remains unclear, and it is the subject of this study. To investigate the role of iASPP in vivo, a transgenic mouse model was generated in which iASPP expression is controlled by the Cre/loxP recombination system. Deletion of iASPP resulted in the development of a cardiocutaneous disorder which displayed features of Arrhythmogenic Right Ventricular Cardiomyopathy (ARVC), defects in hair follicle position and impaired epithelial stratification. iASPP loss resulted in a sudden, premature and arrhythmic mode of death of all iASPP mutant mice. iASPP deficiency induced p53-dependent apoptosis in embryonic hearts and dilation of the right ventricle, however, the inactivation of p53 alleles only rescued the fibro-fatty deposits present in iASPP KO hearts. Mechanistically, iASPP locates at the polar ends of cardiomyocytes where it matches the location of other proteins known to be involved in the etiology of ARVC and in maintaining the integrity of intercalated discs. Loss of iASPP also resulted in increased differentiation of primary keratinocytes both in vitro and in vivo. Consistent with this, iASPP bound p63 and inhibited the transcriptional activity of both TAp63α and ΔNp63 in vitro, and regulated the expression level of p63-regulated genes such as envoplakin. These results demonstrate that iASPP prevents cardiocutaneous disorder through its ability to inhibit p53-induced apoptosis and to influence the integrity of intercalated disc. Moreover, iASPP is also an important regulator of p63 and is involved in controlling epithelial stratification in vivo.